Gender differences in the level and trainability of students' coordination abilities (САs) (review) - Vladimir Lyakh; Tadeusz Ambroży; Anatol Skripko; Song Peng; Michal Spieszny (Journal of Kinesiology and Exercise Sciences)
Background: Analysis and discussion of the studies of authors from different countries and their experimental data on the level and dynamics of development, gender differences, and trainability of different coordination abilities (CAs) in students aged from 18 to 24 years. Methods: The study involved freestyle wrestlers aged 10-13, 14-16, and 17-20 years (n = 127); male (n = 20) and female (n = 10) kickboxers, and male (n = 15) and female (n = 13) taekwondo fighters aged 18 to 27 years; Taekwondo students (n = 24); female (n = 95) and male (n = 65) first-year students of the Faculty of Medicine of the University of Krakow aged 20.1 to 23.5 years. Results: It was found that compared to the somatic indicators and the level of development of abilities related to strength and conditioning (strength, speed, endurance), in which men aged 18-24 years showed significantly higher performance than women (by 10-20% or more), gender differences in the development of CAs are not manifested so obviously and unambiguously. Actually, the development of CAs at the age over 18–19 years without special targeted training and regular training sessions using coordination exercises stops in different sports; when using approximately the same targeted coordination training, approximately the same training potential of male and female students for the improvement of different CAs is observed. Conclusions: The level and rates of improvement of all CAs with age largely depend on the individual characteristics of the students, including their response to the same training load. With age, with an increase in the length of time spent in sports and an increase in performance, a decrease in sex differences in the level of most CAs is observed, which, most likely, can be explained by the similarity of neurophysiological and psychophysiological substrates and mechanisms underlying the optimal control and regulation of complex motor activities.